Observation of higher-order non-Hermitian skin effect - Zhang, Xiujuan; Tian, Yuan; Jiang, Jian-Hua; Lu, Ming-Hui; Chen, Yan-Feng (Nature communications, 2021)
Beyond the scope of Hermitian physics, non-Hermiticity fundamentally changes the topological band theory, leading to interesting phenomena, e.g., non-Hermitian skin effect, as confirmed in one-dimensional systems. However, in higher dimensions, these effects remain elusive. Here, we demonstrate the spin-polarized, higher-order non-Hermitian skin effect in two-dimensional acoustic higher-order topological insulators. We find that non-Hermiticity drives wave localizations toward opposite edges upon different spin polarizations. More interestingly, for finite systems with both edges and corners, the higher-order non-Hermitian skin effect leads to wave localizations toward two opposite corners for all the bulk, edge and corner states in a spin-dependent manner. We further show that such a skin effect enables rich wave manipulation by configuring the non-Hermiticity. Our study reveals the intriguing interplay between higher-order topology and non-Hermiticity, which is further enriched by the pseudospin degree of freedom, unveiling a horizon in the study of non-Hermitian physics. Though non-Hermitian physics has contributed toward the advance of research in quantum, electronic and classical systems, previous work focused on zero- or one-dimensional systems. Here, the authors report higher-order non-Hermitian skin effects in a 2D acoustic higher-order topological insulator.